Using moderated mediation modelling and the interaction of Person-Affect-Cognition-Execution model to explore relationships between psychological distress, specific addictive behaviors, and quality of life across Taiwan, Malaysia, Hong Kong, and China - Huang, Yu Ting; Huang, Po Ching; Hou, Wen Li; Aljaberi, Musheer A.; Gan, Wan Ying; Tung, Serene En Hui; Chen, Ji Kang; Chen, I. Hua; Siaw, Yan Li; Huang, Shih Wei; Chen, Jung Sheng; Lee, Kuo Hsin; et al. (Springer, 2025)
Internet-related addictive behaviors are a public health concern, especially in Asian jurisdictions. Guided by theory, the present study employed moderated mediation modeling using cross-sectional data from Taiwan, Malaysia, Hong Kong, and China to explore relationships between psychological distress, internet-related addictive behaviors, and quality of life (QoL). Jurisdictional differences were also explored. Using snowball sampling to recruit online data, 6,074 participants aged 18 years or older were recruited. Moderated mediation models suggested that psychological distress was related to all internet-related addictive behaviors, and specific behaviors were related to poor QoL in specific domains: gaming addiction to physical and social QoL, shopping addiction to physical, social, and environmental QoL, social networking addiction to all QoL domains, and pornography addiction and gambling addiction to psychological and social QoL (albeit more weakly). Jurisdictional variations were observed, with stronger associations in Taiwan and China compared to Malaysia and Hong Kong. The findings suggest important relationships between psychological distress, internet-related addictive behaviors, and QoL. They also suggest a need for culturally tailored interventions that address psychological distress and specific internet-related addictive behaviors to improve QoL.